Preface - Kotulski, Z.; Sosnowski, W. (Archives of Mechanics, 2009)
This issue of the Archives of Mechanics contains a selection of papers presented at the 36-th Solid Mechanics Conference held in Gdańsk, Poland, on September 9–12, 2008.